Removal of prometryn from hydroponic media using marsh pennywort (Hydrocotyle vulgaris L.). Issue 9 (29th July 2018) - Ni, J.; Sun, S. X.; Zheng, Y.; Datta, R.; Sarkar, D.; Li, Y. M.
ABSTRACT: The aquatic plant Hydrocotyle vulgaris was evaluated for its efficacy in removing prometryn from nutrient solution. Under optimized experimental conditions, up to 94.0% of the initial prometryn was removed from the hydroponic culture medium by H. vulgaris in 30 days. The concentration of prometryn decreased from the initial level of 0.55 ± 0.013 mg/L to 0.036 ± 0.001 mg/L at the end of the experimental period. The removal kinetics followed first-order kinetic equation (Ct = 0.4569e −0.09t ). Half-life (t1/2 ) of prometryn was greatly shortened from 27.16 days (without plant) to 5.58 days (with H. vulgaris). Approximately 22% of the initial prometryn residue was found in H. vulgaris tissue, while 11.7% was degraded by the plant in 30 days. The metabolites of prometryn detected were 2, 4-diamino-1, 3, 5-triazine (in the hydroponic culture medium) and 2, 4, 6-trihydroxy-1, 3, 5-triazine (in plant tissue) after 30 days. The results indicate that H. vulgaris can be used for phytoextraction of prometryn and could potentially be effective in removing other s-trazine pesticides from contaminated aquatic ecosystems.